2019
DOI: 10.1177/000313481908500728
|View full text |Cite
|
Sign up to set email alerts
|

The Understated Malignancy Potential of Nonoperative Acute Appendicitis

Abstract: Cancer of the appendix is rare and is most commonly found incidentally on pathology after an appendectomy for uncomplicated appendicitis (UA). The medical management alternative with antibiotics and observation remains an ongoing debate. The purpose of our study was to develop modern epidemiological data for adult patients completing an appendectomy for UA secondary to an appendiceal neoplasm (AN). ACS-NSQIP database was queried (2005–2016) to identify patients completing an appendectomy. Cohorts of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Primary appendiceal cancer often presents with symptoms similar to acute appendicitis, and postoperative pathology is the gold-standard test for its diagnostic confirmation (16)(17)(18). However, the prognosis of patients with primary appendiceal cancer after surgery and whether chemotherapy is required in these patients are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Primary appendiceal cancer often presents with symptoms similar to acute appendicitis, and postoperative pathology is the gold-standard test for its diagnostic confirmation (16)(17)(18). However, the prognosis of patients with primary appendiceal cancer after surgery and whether chemotherapy is required in these patients are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…16 Nonoperative management of acute appendicitis without an interval appendectomy would lead to worse outcomes in patients with underlying malignancy. 23,24 The literature that identifies interval appendectomy as a risk factor for an appendiceal tumor may be simply reflecting the shift in the management of acute appendicitis with higher rates of nonoperative management. 12,17,18,22 Although several authors have argued against the routine performance of interval appendectomies in patients with complicated appendicitis that experience complete resolution of symptoms, due to the high rates of complications and low risk of recurrence, our data suggests that we would be overlooking the risk of an underlying malignancy when opting out of interval appendectomies, especially in patients older than 40 years with an appendiceal lumen wider than 10 mm on CT. 5,12,25e29 Previous studies have identified various factors associated with malignancy, including age.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers have been eager to adapt this new modality without consideration for possible long-term outcomes, and oncologic ramification. To date, the only gold standard confirmatory test for appendiceal cancer is appendectomy that is usually performed for the presentation of acute appendicitis (26)(27)(28). In a recent prospective study of acute complex appendicitis, patients with complicated appendicitis who underwent either surveillance or interval appendectomy were found to have an exceedingly high rate of malignancy that even resulted in premature discontinuation of a prospective study (14,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%